Alleviation of soil constraints to crop growth in the upland Alfisols and associated soil groups of the West African Sudan savannah by tied ridges - Hulugalle, N.R. (1990)
The climate of the West African Sudan savannah (annual rainfall of 600-900 mm and a monomodal rainy season of 3-4 months) is characterized by frequent long- and short-term droughts. Crop growth in the Alfisols and associated soil groups is further constrained by soil compaction, low soil fertility, high soil temperatures, low soil water retention and available water holding capacity, and low water infiltration rate. Tied ridges, ridges with earthen bunds constructed at right angles to the self-same ridges at intervals of 1-4 m, can alleviate or circumvent the above constraints, and can conserve rainfall received on-site. Water runoff with tied ridging ranges from 0 to 15% of seasonal rainfall, whereas with either open ridging or fiat planting 20-45% of seasonal rainfall is lost as runoff. Soil water content is, therefore, greater with tied ridging. Tied ridging also reduces surface bulk density, maintains soil fertility by reducing losses of soil nutrients in surface runoff and improves soil water retention and available water holding capacity. The water infiltration rate in furrows of tied ridged plots is lower than that with fiat planting or open ridging. With tied ridging, however, rainwater is retained on site by the 'ties', whereas with open ridging or fiat planting it is lost as runoff. Tied ridging increases depth of rooting and subsoil root density in maize (Zea mays), millet (Pennisetum americanum ) and cotton (Gossypium hirsutum) in both wet and dry years, and in cowpea ( Vigna unguiculata ) in dr':, years. Root growth of bambara groundnut ( ILigna subterranea ) is unaffected by tied ridging. Cowpea subsoil root growth is not significantly affected by tied ridging in wet years although root proliferation occurs in the topsoil because of the high sensitivity of cowpea to transient water logging. Vegetative growth and dry matter production of maize, millet, cotton, bambara groundnut, cowpea, groundnut (Arachis hypogaea) and sorghum (Sorghum bicolor) are increased by tied ridging in both wet and dr)' years. Grain yields of maize, millet and sorghum are increased by tied ridging, as is lint production of cotton. Cowpea grain yield is increased only in dry years. Grain yields of bambara groundnut are not significantly affected by tied ridging. Yield responses of groundnut to tied ridges are variable. Growth and yield inhibition may occur in water logging-sensitive crops such as cowpea